Critical Pedagogy of Colombian Physical Education: from socio-critical discourse to pedagogical intervention (Agora for Physical Education and Sport, 2021)
This paper addresses the critical movement of Colombian Physical Education that began to be experienced in the 1960s. Based on the distinction between socio-critical research and critical pedagogy proposed by Kirk (2019), this study argues that the movement resulted in a theoretical renewal that was not eventually expressed in critical pedagogies for the discipline. In methodological terms, the sources are the socio-critical studies present in two Colombian academic journals and two national guidelines for the teaching of Physical Education.
Keywords: Physical Education; Colombia; critical pedagogy; socio-critical studies